Static and dynamic TSEPs of SiC and GaN transistors - Zhu, Siwei; Fayyaz, Asad; Castellazzi, Alberto (2018)
This paper investigates the static and dynamic temperature sensitive electrical parameters (TSEPs) for both SiC and GaN transistors. It is shown that both the qualitative and quantitative temperature characteristics of these parameters are various when different type of transistors are concerned. This finding can be used to select the most appropriate temperature sensitive parameter for the device under specific situation. In this paper, two types of transistors, SiC SCT2080KE MOSFET and GaN PGA26E19BA HEMT are evaluated and compared in terms of six TSEPs, including source-drain reverse bias voltage (VSD), static on-resistance (RDS,ON), gate threshold voltage (VGS(TH)), transconductance (gm), dIDS/dt switching transients and gate current (IG). Then, these TSEPs are compared using four criteria: temperature sensitivity, linearity, material and the capability of on-line temperature monitoring